Strategic Integration of Islamic Values and Educational Marketing to Enhance Madrasah Image: : A Case Study at MTs Al-Amiriyyah - Hafid, Ahmad Nur; Rofiq, Ainur; Aimah, Siti (Belajea: Jurnal Pendidikan Islam, 2024)
Madrasah Tsanawiyah (MTs) plays a vital role in Islamic education, yet it faces challenges related to visibility and competitiveness amid growing public expectations for adaptive and professional educational institutions. This study explores the concrete strategies implemented by MTs Al-Amiriyyah to build its institutional image by integrating Islamic values and modern marketing approaches. We employed a qualitative approach with a case study design. Data were collected through interviews with various informants, including the school principal, teachers, staff, foundation administrators, school treasurer, students, and alumni, as well as through participatory observation and documentation. The data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that MTs Al-Amiriyyah applies the 7P marketing mix strategy in a contextualized manner, such as through promotion through social media, flagship programs rooted in Islamic values such as tahfiz, language development, and digitalization, as well as transparent and responsive public services. These strategies have successfully enhanced the institution’s image as an adaptive and competitive Islamic educational provider.